MEMANFAATKAN KARUNGUT SEBAGAI SARANA MENUMBUHKEMBANGKAN NILAI-NILAI PANCASILA - Basori, B; Akbar, Taufik (ppjbsip, 2024)
Karungut is a creation that the Dayak people uphold as a great classical literature and is a kind of pantun or gurindam. The singer of karungut tells poems by mixing various legends, advices, admonitions, and warnings about everyday life. Indonesian society faces serious challenges related to nationalism, diversity, and the diminution of Pancasila values in the life of nation and state. This paper seeks to explore the potential of karungut to be utilized as one of the tools to instill and nurture the values of Pancasila in the life of society.